THE INFLUENCE OF ECONOMIC INEQUALITY, UNEMPLOYMENT RATE, AND POVERTY ON THEFT CRIMES: AN EMPIRICAL LITERATURE STUDY IN INDONESIA - Gunawan Widjaja; Junior B. Gregorius (Review of International Economy and Finance, 2026)
This study aims to analyse the influence of economic inequality, unemployment rates, and poverty on theft crimes in Indonesia through an empirical literature review. Using a thematic synthesis approach to various journals and research reports, this study found that economic inequality and unemployment rates have a significant positive influence on the increase in theft crime rates. Poverty also contributes to the risk of theft, especially when the economic pressure felt by the community is very high. The results of the study indicate that the combination of these three variables strengthens the potential for theft crimes in Indonesia, thus requiring policies that focus on reducing inequality, creating jobs, and implementing poverty alleviation programmes to effectively reduce crime rates.